Process for insert casting hard metal into a breaking hammer head

CN122938253APending Publication Date: 2026-10-20广东泰邦耐磨金属科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611006739.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-07
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

本发明采用真空液相烧结预制TiC基钢结硬质合金,相对致密度可达98%以上,TiC颗粒分布均匀、晶粒尺寸稳定,避免了原位自蔓延反应晶粒粗大、孔隙多、性能波动大的缺陷。配合表面渗硼抗熔蚀层,有效阻隔高温钢液对硬质相的熔蚀破坏,使硬质合金在镶铸后仍保持HRC60以上的高硬度,耐磨性能稳定可靠。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

This invention relates to the field of wear-resistant material casting technology, specifically a process for inlaying cemented carbide into a hydraulic breaker hammer. The process includes the following steps: First, a uniformly dense TiC-based steel-bonded cemented carbide preform is prepared by vacuum liquid-phase sintering. This preform is then subjected to solid boronizing and plasma-sprayed nickel-based coating treatments to form a gradient-modified surface. Next, the preform is fixed to the working surface of a lost foam casting mold with an inclined, staggered structure at 30°–45° to the impact direction. After stepped gradient preheating, bottom-pouring staged casting combined with ultrasonic vibration is used to complete the inlaying process. Finally, the finished product is obtained through graded water toughening and low-temperature stress-relief tempering. This invention replaces the in-situ self-propagating reaction with a pre-sintered preform, and, combined with gradient interface modification and inclined biomimetic arrangement, solves the problems of uneven hard phase structure, uncontrolled interface melting, and insufficient impact and wear resistance in existing in-situ synthesis processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of wear-resistant material casting technology, specifically a process for inserting cemented carbide into a crusher hammer. Background Technology

[0002] Hammer crusher hammers are core wear parts in industries such as mining, building materials, and metallurgy. They withstand both high-speed impacts and abrasive wear, and their performance directly determines production efficiency and maintenance costs. To balance wear resistance and toughness, the industry widely adopts cemented carbide composite hammer technology, which mainly falls into two technical routes: pre-cast cemented carbide and in-situ reaction synthesis.

[0003] In the prior art, invention patent CN102423799B discloses a method for in-situ synthesis of steel-bonded cemented carbide casting composite hammerheads. This method involves preparing a paste from Ti powder, graphite powder, W powder, and metal powder, filling it into grooves in an EPS mold, and utilizing the high temperature of the poured molten steel to initiate a self-propagating reaction, generating TiC and WC hard phases in situ. This process eliminates the need for prefabricated cemented carbide blocks, simplifying the process. However, in practical engineering applications, the following problems still exist: (1) The in-situ self-propagating reaction is fast and the temperature gradient is large. The TiC / WC grains generated are easy to be coarse and have poor distribution uniformity. Pores are easy to remain inside. The density of the cemented carbide region is usually less than 92%, the wear resistance fluctuates greatly, and it is difficult to stably exert the strengthening effect of the hard phase.

[0004] (2) When powder paste comes into direct contact with high-temperature molten steel, the diffusion of elements during the reaction is uncontrollable, which can easily lead to excessive melting of hard phase or concentration of brittle phase at the interface. At the same time, there is a lack of interface wetting and strengthening methods, and the interface is prone to residual pores and inclusions. The metallurgical bonding layer is uneven in thickness, and the bonding strength fluctuates greatly. Under impact load, the hard alloy area is prone to fall off as a whole.

[0005] To address the aforementioned problems, we propose a cemented carbide inlay process for hammerheads. Summary of the Invention

[0006] The purpose of this invention is to provide a process for inserting cemented carbide into a breaker hammer head to solve the problems mentioned in the background art.

[0007] To achieve the above objectives, the present invention provides the following technical solution: A process for inserting cemented carbide into a breaker hammer head includes the following steps: S1: TiC-based steel-bonded cemented carbide preforms were prepared by cold isostatic pressing and vacuum liquid phase sintering using TiC particles as the hard phase and high-manganese steel powder as the binder phase. Solid boronizing treatment and plasma spraying nickel-based alloy coating treatment were performed on the surface of the preforms in sequence to form a gradient modified structure from the inside to the outside, consisting of cemented carbide matrix, titanium boride anti-corrosion layer, and nickel-based wetting transition layer. S2: The hammer mold is prepared by lost foam casting process. The gradient modified cemented carbide preform is positioned and fixed in the working area of ​​the mold according to the inclined staggered structure, so that the axis of the preform is at an angle of 30° to 45° with the impact force direction of the hammer. After coating with refractory coating, it is dried and buried in the box to complete the negative pressure molding. S3: Perform two-stage stepped gradient preheating on the mold, and at the same time melt high manganese steel matrix molten steel in medium frequency induction furnace, and add rare earth ferrosilicon alloy for modification treatment after adjusting the composition. S4: The bottom-pouring step-by-step casting process is adopted. First, a portion of the molten steel is injected at a low speed to completely immerse the precast part. Then, the ultrasonic vibration device arranged on the side wall of the sand box is turned on for auxiliary treatment. Finally, the remaining molten steel is injected at a medium speed to complete the filling process, so as to realize the metallurgical bonding and casting of the precast part and the substrate. S5: After the casting is kept warm and cooled slowly, it is unpacked and cleaned, and then subjected to graded heating water toughening treatment and low-temperature stress relief tempering to obtain the finished crusher hammer.

[0008] Furthermore, in S1, the specific process of preform preparation and gradient modification is as follows: Weigh out 50%–60% TiC particles, 25%–35% high-manganese steel powder, 2%–4% molybdenum powder, 1.5%–3% chromium powder, and 0.5%–1% graphite powder by mass fraction, and place them in a planetary ball mill for 8–12 hours of ball-to-powder mixing at a ball-to-powder ratio of 5:1 using anhydrous ethanol as the medium. After mixing, vacuum dry and sieve the mixture, then place it into a rubber mold and cold isostatically press it under 200 MPa pressure to obtain a cylindrical green blank. Place the green blank in a vacuum sintering furnace and hold it at 1400–1430℃ for 90–120 minutes for liquid-phase sintering. After furnace cooling, obtain a TiC-based steel-bonded cemented carbide preform with a density ≥98%. The pre-sintering process makes the hard phase structure uniform and controllable, with a density much higher than that of cemented carbide generated by in-situ reaction, providing a basis for high wear resistance.

[0009] After cleaning the surface oil of the precast component, it is embedded in a solid boronizing agent, which consists of 20% ferroborone, 5% boron carbide, 70% alumina, and 5% potassium fluoroborate by mass fraction. The boronizing box is placed in a box furnace, heated to 850–900℃ and held for 3–5 hours. After cooling with the furnace, it is cleaned, forming a 15–30 μm thick titanium boride anti-corrosion layer on the surface of the precast component. Titanium boride has excellent thermal stability, which can effectively prevent the high-temperature molten steel from eroding the interior of the precast component, avoid the dissolution and coarsening of TiC particles, and stabilize the properties of the hard phase.

[0010] A nickel-based alloy transition coating was prepared on the surface of boron-diffused preforms using plasma spraying. The spraying power was 35–45 kW, the spraying distance was 100–130 mm, and the coating thickness was 80–120 μm. The coating composition, by mass fraction, was 65%–75% Ni, 10%–15% Cr, 5%–10% Fe, 2%–4% B, 2%–3% Si, and 0.5%–1% rare earth Ce. The nickel-based coating has a lower melting point than high-manganese steel, and it melts preferentially during casting, undergoing elemental interdiffusion with the molten steel, significantly improving wettability. B and Si elements can deoxidize and reduce surface tension, decreasing interfacial porosity. Rare earth elements can purify grain boundaries and refine interfacial structure, collectively promoting the formation of a dense and uniform metallurgical bonding layer.

[0011] Furthermore, in S2, the specific method of the inclined staggered arrangement is as follows: Multiple cylindrical cemented carbide preforms are arranged in a staggered, quincunx pattern along the length and height of the hammerhead, with the axial distance between adjacent preforms being 2.5 to 3.5 times the diameter of the preform. This staggered arrangement creates an alternating concave-convex wear-resistant structure on the working surface, generating eddy currents to buffer material impact and reduce direct erosion of the substrate.

[0012] The precast component's axis forms a 30°–45° angle with the hammer's impact force direction, and its embedding depth into the working surface is 1 / 2–2 / 3 of its own length, with the exposed end facing the interior of the casting. This inclined arrangement allows the cemented carbide to bear wear with a beveled cross-section, increasing the effective wear area by more than 40% compared to a vertical arrangement. Simultaneously, the impact load is decomposed along the axial direction, reducing the risk of bending fracture in the cemented carbide. As the matrix wears, the cemented carbide always presents its wear-resistant end face to the material, ensuring consistently stable wear resistance. High-temperature resistant ceramic locating pins are used to fix the precast component's end within the positioning groove of the lost foam pattern, ensuring positional accuracy during casting and preventing precast component drift.

[0013] Furthermore, in S2, the specific process of lost foam negative pressure molding is as follows: The hammerhead body is fabricated using EPS foam boards, and inclined positioning grooves matching the precast parts are machined at corresponding positions on the working surface. After the precast parts are assembled, a layer of zircon powder refractory coating is first applied as the top layer to ensure surface smoothness and resistance to molten steel erosion; after natural drying, a layer of quartz powder refractory coating is applied as the back layer to improve air permeability and strength. The total coating thickness is 1.5–2.5 mm.

[0014] After the coating has air-dried naturally, it is placed in a drying kiln at 50–60℃ for 12–24 hours to completely remove moisture. The dried pattern is then placed in a sand box, filled with 30–50 mesh dry sand, and compacted using a three-dimensional vibration table at a frequency of 50Hz for 2–3 minutes. The top is then covered with a sealing plastic film and connected to a negative pressure system, maintaining a negative pressure of 0.04–0.06 MPa to complete the molding process. Lost foam casting with negative pressure provides high dimensional accuracy and good yielding properties, and can alleviate the stress caused by cooling and shrinkage of the casting.

[0015] Furthermore, in S3, the specific process of the two-stage stepped gradient preheating is as follows: The molded sand box is fed into a bogie-type preheating furnace. In the first stage, the temperature is increased to 200℃ at a rate of 5–8℃ / min and held for 1–2 hours to thoroughly remove residual moisture and crystal water from the mold and coating, preventing gas generation and porosity defects during pouring. In the second stage, the temperature is increased to 400–450℃ at a rate of 3–5℃ / min and held for 2–3 hours to ensure uniform temperature throughout the mold. This stepped heating prevents cracking due to thermal shock while ensuring a sufficient initial temperature, reducing the cooling rate of the molten steel during filling, extending the liquid residence time at the interface, and promoting element diffusion and metallurgical bonding. After preheating, the mold exiting the furnace at a temperature no lower than 350℃, and pouring begins within 10 minutes to prevent excessive temperature drop from affecting the interface bonding.

[0016] Furthermore, in S3, the specific process of steel molten smelting and modification treatment is as follows: Pig iron, scrap steel, high-carbon ferromanganese, and low-carbon ferrochrome are added to the ZGMn13 mixture according to the specified proportions, and the mixture is heated to 1520–1560℃ in a medium-frequency induction furnace until completely melted. Samples are taken for analysis and the chemical composition is adjusted to ensure the molten steel meets the following mass fractions: C 1.0%–1.4%, Mn 11%–14%, Si 0.3%–0.8%, Cr 1.0%–2.0%, P ≤ 0.07%, and S ≤ 0.05%. The addition of chromium improves the hardenability and work hardening capacity of the matrix, and enhances its wear resistance.

[0017] Five to ten minutes before tapping, 0.2% to 0.4% of rare earth ferrosilicon alloy by mass of the molten steel is added to the furnace for modification treatment. Rare earth elements can desulfurize and deoxidize the molten steel, purify the solidification structure, and further improve the wettability of the molten steel to the surface of cemented carbide. After settling and slag removal, the temperature of the molten steel is adjusted to 1420–1460℃, a temperature range that balances filling fluidity and interface erosion control.

[0018] Furthermore, in S4, the specific process of ultrasonic-assisted stepwise casting is as follows: A bottom-pouring gating system is used, allowing molten steel to rise steadily from the bottom of the mold, avoiding turbulent air entrapment and direct erosion of the preforms. First, molten steel accounting for 30% to 40% of the total mass is poured in at a low speed of 0.8 to 1.2 kg / s, so that the molten steel can smoothly submerge all cemented carbide preforms, allowing the interface area to be fully preheated and initiating element diffusion.

[0019] Turn on the ultrasonic vibration device arranged on the side wall of the sand box, with a vibration frequency of 20-30 kHz and a power density of 0.5-1.0 W / cm², and continue vibration for 30-60 seconds. The cavitation effect and acoustic flow generated by ultrasonic vibration can break up the oxide film and inclusions at the interface, promote the full wetting of the molten steel and the coating, accelerate the interdiffusion of elements such as Mn, Fe, and Ni, and make the metallurgical bonding layer thicker and more uniform; at the same time, it refines the matrix structure near the interface, reduces component segregation, and reduces the tendency for hot cracking.

[0020] Keep the ultrasonic vibration on and inject the remaining molten steel into the mold at a medium speed of 1.5-2.0 kg / s until the mold is full. After it is full, continue to vibrate for 10-20 seconds and then turn off the ultrasonic device to ensure that the filling is stable and the interface reaction is sufficient.

[0021] Furthermore, in step S5, the specific process of graded water toughening treatment and low-temperature tempering is as follows: After casting, the part is kept warm and slowly cooled in the sand box to below 300℃ before being opened to avoid excessive thermal stress caused by rapid cooling. After opening the box and cleaning the gating gate and surface sand, it is immediately sent to a box-type heat treatment furnace and heated to 600℃ at a rate of 10-15℃ / min. It is held at this temperature for 1-2 hours to homogenize the temperature, eliminate the internal temperature gradient of the casting, and prevent interfacial thermal stress cracking caused by rapid heating.

[0022] Continue heating to 1050–1100℃ and hold for 2–4 hours to fully austenitize the matrix and dissolve the carbides. Quickly immerse the casting in a water-cooling bath at 20–40℃. Once the surface temperature of the casting is below 100℃, remove it to obtain a supersaturated austenitic structure, ensuring high toughness and excellent work hardening ability of the matrix.

[0023] The water-quenched castings are placed in a tempering furnace and held at 200–250°C for 3–5 hours for stress-relief tempering. After cooling to room temperature in the furnace, they are removed from the furnace. Low-temperature tempering can eliminate residual internal stress generated by water quenching, stabilize microstructure dimensions, and further improve the interfacial impact fatigue resistance.

[0024] Compared with the prior art, the beneficial effects of the present invention are: This invention employs vacuum liquid-phase sintering to prefabricate TiC-based steel-bonded cemented carbide, achieving a relative density of over 98%. The TiC particles are uniformly distributed and have stable grain sizes, avoiding the defects of in-situ self-propagating reactions such as coarse grains, numerous pores, and large performance fluctuations. Combined with a surface boron-diffused anti-corrosion layer, it effectively prevents the high-temperature molten steel from eroding and damaging the hard phase, allowing the cemented carbide to maintain a high hardness of HRC60 or higher after casting, with stable and reliable wear resistance.

[0025] This invention constructs a gradient modified structure of "titanium boride anti-corrosion layer + nickel-based wetting transition layer," which not only resists steel molten corrosion and protects the hard phase, but also significantly improves interfacial wettability through the nickel-based coating. Combined with ultrasonic vibration-assisted casting, it breaks up interfacial oxidative inclusions and promotes element interdiffusion, forming a uniform and dense metallurgical bonding layer with an interfacial shear strength exceeding 480 MPa, far higher than the bonding strength of in-situ synthesis processes, fundamentally solving the problem of cemented carbide detachment failure.

[0026] This invention employs an inclined, staggered arrangement of the axis at 30°–45° to the impact direction, increasing the effective wear area by more than 40% compared to a vertical groove structure. Simultaneously, it decomposes the impact load, reducing the risk of bending fracture in the cemented carbide. As wear progresses, the cemented carbide always faces the material with its wear-resistant end face. Combined with the staggered, uneven wear-resistant structure, this achieves a self-sharpening effect during wear, simultaneously improving material utilization and wear life.

[0027] This invention effectively mitigates residual thermal stress caused by the difference in thermophysical properties between cemented carbide and the steel matrix through a full-process stress control process involving stepped mold preheating, sand box slow cooling, graded heating water quenching, and low-temperature stress-relief tempering, thereby reducing the risk of interface cracking. Combined with rare-earth modification to refine the matrix structure, the hammerhead possesses both a high-hardness, wear-resistant working surface and a high-toughness matrix, exhibiting excellent impact fatigue resistance. Under high-impact crushing conditions, its service life is increased by more than 60% compared to in-situ synthesized composite hammerheads. Attached Figure Description

[0028] Figure 1 This is a schematic diagram of the process for inserting cemented carbide into a breaker hammer head according to the present invention. Detailed Implementation

[0029] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Example

[0030] This embodiment provides a process for inserting cemented carbide into a breaker hammerhead, and the specific steps are as follows: Step 1: Preparation and gradient modification of cemented carbide preforms: Weigh out 55% TiC particles, 30% high-manganese steel powder, 3% molybdenum powder, 2% chromium powder, and 1% graphite powder by mass fraction, and place them in a planetary ball mill for 8 hours to mix. The ball-to-powder ratio is 5:1, and anhydrous ethanol is used as the medium. After mixing, vacuum dry and pass through a 100-mesh sieve. Place the mixture into a rubber mold and cold isostatically press it at 200 MPa to obtain a cylindrical green body with a diameter of 16 mm and a length of 60 mm. Sinter the green body in a vacuum sintering furnace at 1420℃ for 100 min for liquid phase sintering. After cooling in the furnace, the preform is obtained. The relative density is 98.7%, the hardness is HRC62, and the flexural strength is 1920 MPa.

[0031] After cleaning, the preform was embedded with a solid boronizing agent (20% ferroboron, 5% boron carbide, 70% alumina, and 5% potassium fluoroborate) and held at 880℃ for 4 hours for boronizing, resulting in a titanium boride layer approximately 22 μm thick on the surface. A nickel-based coating was prepared by plasma spraying at a power of 40 kW and a distance of 120 mm, achieving a coating thickness of approximately 100 μm. The coating composition, by mass fraction, was: Ni 70%, Cr 12%, Fe 8%, B 3%, Si 2.5%, and Ce 0.8%.

[0032] Step 2: Lost foam casting and precast component positioning: The shape of a 20kg crusher hammer is made from EPS board, and the working surface is machined with inclined positioning grooves. The prefabricated parts are arranged in a staggered, quincunx pattern at a 35° angle, with an adjacent axis spacing of 45mm and an embedding depth of 35mm, and are fixed with ceramic positioning pins.

[0033] Apply a zircon powder topcoat and a quartz powder backcoat, with a total thickness of approximately 2mm. Allow it to air dry naturally, then bake it at 55℃ for 18 hours. Place the pattern in a sand box, fill it with 40-mesh dry sand, and compact it with three-dimensional vibration for 2.5 minutes. After sealing, apply a negative pressure to 0.05MPa.

[0034] Step 3: Mold preheating and molten steel melting: The sand box is fed into the preheating furnace. In the first stage, the temperature is increased to 200℃ at a rate of 6℃ / min and held for 1.5 hours. In the second stage, the temperature is increased to 420℃ at a rate of 4℃ / min and held for 2.5 hours. The temperature at the furnace outlet is about 400℃, and the sand box is then transferred to the casting station.

[0035] High-manganese steel was smelted in a 500kg medium-frequency furnace. After melting at 1540℃, the composition was adjusted to: C 1.2%, Mn 12.5%, Si 0.5%, Cr 1.5%, P 0.04%, S 0.03%. 8 minutes before tapping, 0.3% rare earth ferrosilicon alloy was added for modification. After slag removal, the temperature was adjusted to 1440℃.

[0036] Step 4: Ultrasonic-assisted stepwise casting: For bottom-pouring casting, approximately 7 kg of molten steel is first injected at a rate of 1.0 kg / s to immerse the precast component; ultrasonic vibration is then activated at a frequency of 25 kHz and a power density of 0.8 W / cm² for 45 seconds; with the ultrasonic vibration still on, the remaining molten steel is injected at a rate of 1.8 kg / s to fill the component, and vibration continues for 15 seconds after filling before being turned off. The entire casting process is conducted under stable negative pressure.

[0037] Step 5, graded heat treatment: After pouring, the casting is held under pressure for 1 hour and then allowed to cool naturally to 280°C before being unpacked and cleaned. The casting is then placed in the furnace and heated to 600°C at a rate of 12°C / min, where it is held for 1.5 hours. The temperature is then further increased to 1080°C and held for 3 hours for austenitization. The casting is then rapidly quenched in water at 30°C until the surface temperature reaches 80°C, at which point it is removed from the furnace. Subsequently, it is subjected to stress-relief tempering at 220°C for 4 hours and then cooled in the furnace to room temperature before being removed from the furnace. Example

[0038] The process steps in this embodiment are basically the same as those in Embodiment 1, except that: Precast component composition: TiC 52%, high manganese steel powder 33%, molybdenum powder 2.5%, chromium powder 2%, graphite powder 0.5%; sintering process: 1410℃ for 110 min; finished product hardness: HRC61.

[0039] The boronizing process involves holding the titanium boride layer at 860℃ for 5 hours, resulting in a titanium boride layer thickness of approximately 28 μm and a nickel-based coating thickness of 90 μm.

[0040] The precast components are arranged at an angle of 40°, and the distance between adjacent axes is three times the diameter.

[0041] The mold was preheated to a final temperature of 400℃ and held for 3 hours; the pouring temperature was 1430℃, the ultrasonic power density was 0.6W / cm², and the vibration lasted for 50 seconds.

[0042] Water quenching temperature 1060℃, hold for 3.5 hours; tempering temperature 200℃, hold for 5 hours. Example

[0043] The process steps in this embodiment are basically the same as those in Embodiment 1, except that: Precast component composition: TiC 58%, high manganese steel powder 27%, molybdenum powder 3.5%, chromium powder 2.5%, graphite powder 1%; sintering process: 1430℃ for 90 minutes, finished product hardness HRC64.

[0044] The boronizing process involves holding the titanium boride layer at 900℃ for 3 hours, resulting in a titanium boride layer thickness of approximately 18μm and a nickel-based coating thickness of 110μm.

[0045] The precast components are arranged at an angle of 30°, and the distance between adjacent axes is 2.8 times the diameter.

[0046] The mold was preheated to a final temperature of 450℃ and held for 2 hours; the pouring temperature was 1450℃, the ultrasonic power density was 1.0W / cm², and the vibration lasted for 35 seconds.

[0047] Water quenching temperature 1100℃, hold for 2 hours; tempering temperature 250℃, hold for 3 hours.

[0048] Comparative examples (prepared according to the process described in reference document CN102423799B) Comparative sample was prepared according to the method in Example 1 of the comparative document: Ti powder, graphite powder, W powder, and metal powder were weighed and mixed, and a polyvinyl alcohol aqueous solution was added to make a paste. This paste was filled into the vertical grooves of the EPS hammerhead mold, coated with magnesia powder paint, and dried at 45°C for 36 hours. High-chromium cast iron molten steel was poured into the vacuum lost foam casting process, utilizing the high-temperature in-situ generation of TiC+WC cemented carbide from the molten steel. The casting was then normalized at 900°C and tempered at 400°C to obtain the finished product.

[0049] Performance testing and comparison: The performance of the samples from the three sets of examples and one set of comparative examples was tested. The test items included interfacial shear strength, average hardness of the working surface, matrix impact toughness, and density of the cemented carbide region. An on-machine wear test was conducted under the same limestone crushing conditions. The relative wear resistance (based on a common high-manganese steel hammerhead, with higher values ​​indicating better wear resistance) and cemented carbide shedding rate were statistically analyzed. The results are shown in the table below. Interfacial shear strength (MPa) 482 465 471 320 Average hardness of working surface (HRC) 60 59 62 54 Matrix impact toughness (J / cm²) 135 142 126 110 Density (%) of cemented carbide regions 98.7 98.2 98.9 91.5 Relative wear resistance (high manganese steel = 1) 4.2 3.9 4.7 2.6 Carbide shedding rate (%) 0 0 0 12.5 The data in the table above shows that: The density of the cemented carbide regions in the embodiments of the present invention is all above 98%, which is much higher than the 91.5% of the comparative example. This indicates that the pre-sintering process can obtain a more dense and stable hard phase, thereby improving wear resistance from the source.

[0050] The interfacial shear strength of the embodiments was all above 460 MPa, which is more than 45% higher than that of the comparative example. Moreover, no cemented carbide fell off during the installation test, which proves that the interfacial strengthening effect of gradient modification + ultrasonic assistance is significant and the metallurgical bonding quality is far superior to that of the in-situ synthesis process.

[0051] The relative wear resistance of the embodiment can reach 3.9 to 4.7 times, which is 50% to 80% higher than that of the comparative example, while the matrix maintains excellent impact toughness, achieving a good balance between wear resistance and impact resistance.

[0052] By adjusting the composition and process parameters, the three sets of embodiments can be adapted to crushing conditions with different impact levels, demonstrating good engineering adaptability.

[0053] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A process for inlaying cemented carbide into a breaker hammerhead, characterized in that, Includes the following steps: S1: TiC-based steel-bonded cemented carbide preforms were prepared by cold isostatic pressing and vacuum liquid phase sintering using TiC particles as the hard phase and high-manganese steel powder as the binder phase. Solid boronizing treatment and plasma spraying nickel-based alloy coating treatment were performed on the surface of the preforms in sequence to form a gradient modified structure from the inside to the outside, consisting of cemented carbide matrix, titanium boride anti-corrosion layer, and nickel-based wetting transition layer. S2: The hammer mold is prepared by lost foam casting process. The gradient modified cemented carbide preform is positioned and fixed in the working area of ​​the mold according to the inclined staggered structure, so that the axis of the preform is at an angle of 30° to 45° with the impact force direction of the hammer. After coating with refractory coating, it is dried and buried in the box to complete the negative pressure molding. S3: Perform two-stage stepped gradient preheating on the mold, and at the same time melt high manganese steel matrix molten steel in medium frequency induction furnace, and add rare earth ferrosilicon alloy for modification treatment after adjusting the composition. S4: The bottom-pouring step-by-step casting process is adopted. First, a portion of the molten steel is injected at a low speed to completely immerse the precast part. Then, the ultrasonic vibration device arranged on the side wall of the sand box is turned on for auxiliary treatment. Finally, the remaining molten steel is injected at a medium speed to complete the filling process, so as to realize the metallurgical bonding and casting of the precast part and the substrate. S5: After the casting is kept warm and cooled slowly, it is unpacked and cleaned, and then subjected to graded heating water toughening treatment and low-temperature stress relief tempering to obtain the finished crusher hammer.

2. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In step S1, the specific process of preform preparation and gradient modification is as follows: Weigh out 50%–60% TiC particles, 25%–35% high manganese steel powder, 2%–4% molybdenum powder, 1.5%–3% chromium powder, and 0.5%–1% graphite powder by mass fraction. After ball milling and cold isostatic pressing at 200 MPa, liquid phase sintering is carried out under vacuum conditions at 1400–1430℃ for 90–120 min to obtain cylindrical cemented carbide preforms. The preform is embedded in a solid boronizing agent composed of ferroboron, boron carbide, alumina and potassium fluoroborate, and kept at 850-900℃ for 3-5 hours to form a titanium boride anti-corrosion layer with a thickness of 15-30μm on the surface of the preform. A nickel-based alloy transition coating was prepared on the surface of the boron-diffused preform using a plasma spraying process. The coating thickness was 80–120 μm, and the coating composition was as follows (by mass fraction): Ni 65%–75%, Cr 10%–15%, Fe 5%–10%, B 2%–4%, Si 2%–3%, and rare earth Ce 0.5%–1%.

3. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In S2, the specific method of the inclined staggered arrangement is as follows: Multiple cylindrical cemented carbide preforms are arranged in a staggered, quincunx pattern along the length and height of the hammerhead, with the axial spacing between adjacent preforms being 2.5 to 3.5 times the diameter of the preform. The precast part is embedded in the working surface to a depth of 1 / 2 to 2 / 3 of its own length, with the exposed end facing the inside of the casting. High-temperature resistant ceramic positioning pins are used to fix the end of the precast part in the positioning groove of the lost foam pattern.

4. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In S2, the specific process of lost foam negative pressure molding is as follows: The hammerhead body is made of EPS foam board, and inclined positioning grooves that match the prefabricated parts are machined at the corresponding positions on the working surface. After the prefabricated components are assembled, zircon powder topcoat and quartz powder backcoat are applied in sequence, with a total coating thickness of 1.5 to 2.5 mm. After air drying, place it in a drying kiln at 50-60℃ for 12-24 hours, put it into a sand box, fill it with dry sand and compact it with three-dimensional vibration, seal the top and connect it to a negative pressure system to maintain a negative pressure of 0.04-0.06MPa to complete the shaping.

5. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In S3, the specific process of the two-stage stepped gradient preheating is as follows: The first stage involves heating to 200℃ at a rate of 5–8℃ / min and holding at that temperature for 1–2 hours to remove residual moisture from the mold. In the second stage, the temperature is increased to 400-450℃ at a rate of 3-5℃ / min, and held for 2-3 hours to ensure uniform temperature throughout the mold. After preheating, the temperature of the mold exiting the furnace should not be lower than 350℃, and pouring should begin within 10 minutes.

6. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In step S3, the specific process of steel molten metal smelting and modification treatment is as follows: The steel is prepared according to the ZGMn13 composition and heated to 1520–1560℃ in a medium-frequency induction furnace until completely melted. The chemical composition is adjusted to ensure that the molten steel meets the following mass fraction requirements: C 1.0%–1.4%, Mn 11%–14%, Si 0.3%–0.8%, Cr 1.0%–2.0%, P ≤ 0.07%, and S ≤ 0.05%. Five to ten minutes before tapping, 0.2% to 0.4% of rare earth ferrosilicon alloy by mass of molten steel is added for modification treatment. After settling and slag removal, the pouring temperature is adjusted to 1420 to 1460℃.

7. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In S4, the specific process of ultrasonic-assisted stepwise casting is as follows: A bottom-pouring casting system is adopted. First, molten steel accounting for 30% to 40% of the total mass is injected at a flow rate of 0.8 to 1.2 kg / s, so that the molten steel rises steadily and completely submerges all cemented carbide preforms. Turn on the ultrasonic vibration device, set the vibration frequency to 20–30 kHz, the power density to 0.5–1.0 W / cm², and continue vibration for 30–60 seconds. Keep the ultrasonic vibration on and inject the remaining molten steel into the mold at a flow rate of 1.5 to 2.0 kg / s until the mold is full. After it is full, continue to vibrate for 10 to 20 seconds and then turn off the ultrasonic device.

8. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, In step S5, the specific process of graded water toughening treatment and low-temperature tempering is as follows: After the casting is poured, it is kept warm in the sand box and slowly cooled to below 300°C before being unpacked and sent to the heating furnace. The temperature is raised to 600°C at a rate of 10-15°C / min and held for 1-2 hours to achieve uniform temperature. Continue heating to 1050–1100℃ and hold for 2–4 hours to fully austenitize the matrix; Quickly lower the casting into a water-cooling tank, with the water temperature controlled between 20 and 40°C. Remove the casting once the surface temperature of the casting is below 100°C. After water toughening, the castings are sent to a tempering furnace and held at 200-250℃ for 3-5 hours for stress relief tempering. After cooling to room temperature in the furnace, they are taken out of the furnace.

9. The process for inserting cemented carbide into a breaker hammer head according to claim 2, characterized in that, The cemented carbide preform has a relative density of ≥98% after sintering, a hardness of HRC60~65, and a bending strength of ≥1800MPa.

10. The process for inserting cemented carbide into a breaker hammer head according to claim 1, characterized in that, The finished crusher hammer has an interfacial shear strength ≥480MPa, an average working surface hardness ≥HRC58, and a matrix impact toughness ≥120J / cm². Under the same limestone crushing conditions, its service life is increased by more than 60% compared with the in-situ synthesized steel-bonded cemented carbide composite hammer.

Citation Information

Patent Citations

  • Method of in situ synthetic steel bond hard alloy casting composite hammerhead and hammerhead

    CN102423799B